2012
DOI: 10.1007/s00228-012-1259-9
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-induced nephrotoxicity: mechanism, incidence, risk factors and special populations. A literature review

Abstract: Vancomycin-induced renal toxicity was reported in 10-20 % and 30-40 % of patients following conventional and high doses of vancomycin therapy, respectively .The most probable mechanism for its nephrotoxicity can be at least partially attributable to an increased production of reactive oxygen species and oxidative stress. There are a number of different risk factors which could accelerate or potentiate the occurrence of vancomycin-induced nephrotoxicity, with the most documented risk factors being high trough v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
307
5
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(335 citation statements)
references
References 74 publications
9
307
5
14
Order By: Relevance
“…Although some have proposed the routine addition of vancomycin to the preoperative antibiotic regimen, we and others have shown that the addition of this additional drug did not reduce the incidence of SSI compared with a single drug regimen [33,36,39]. Additionally, vancomycin overuse can result in adverse events including nephrotoxicity, ototoxicity, and the development of resistant organisms [2,13,40]. Therefore, the purposes of this study are to (1) compare risk of developing AKI between patients receiving prophylactic cefazolin versus without the addition of vancomycin; (2) compare the severity and recovery of AKI in these cohorts; and (3) determine the independent risk factors for AKI in patients undergoing primary hip and knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some have proposed the routine addition of vancomycin to the preoperative antibiotic regimen, we and others have shown that the addition of this additional drug did not reduce the incidence of SSI compared with a single drug regimen [33,36,39]. Additionally, vancomycin overuse can result in adverse events including nephrotoxicity, ototoxicity, and the development of resistant organisms [2,13,40]. Therefore, the purposes of this study are to (1) compare risk of developing AKI between patients receiving prophylactic cefazolin versus without the addition of vancomycin; (2) compare the severity and recovery of AKI in these cohorts; and (3) determine the independent risk factors for AKI in patients undergoing primary hip and knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effectiveness and superiority of the addition of vancomycin to the standard prophylactic regimen in infection prevention continues to be debated [33,36,37,39]. Finally, exposure to vancomycin has been shown to be a risk factor for the development of resistant organisms, hearing loss, and acute kidney injury (AKI) [2,13,14,40]. Therefore, the purposes of this study are to (1) compare risk of developing AKI between patients receiving prophylactic cefazolin with versus without the addition of vancomycin; (2) compare the severity and recovery of AKI in these cohorts; and (3) determine the independent risk factors for AKI in patients undergoing primary hip and knee arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is a broad-spectrum antibiotic known to be effective against the USA300 strain of MRSA (80), the same strain used in our studies. It is used selectively prior to surgery (54), as it has been suggested to induce renal toxicity; however, this is not known to happen after single-dose administration (81). Vancomycin has also been shown to increase mast cell degranulation (82), which is associated with delayed-type hypersensitivity and renal toxicity (83).…”
Section: Discussionmentioning
confidence: 99%
“…Th e American Th oracic Society and the Infectious Diseases Society of America recommend vancomycin trough levels between 15 and 20 mg/L for hospital and ventilatorassociated pneumonias, bacteremia, endocarditis, osteomyelitis, and meningitis ( 7 ). Treatment with vancomycin beyond 1 week increases the incidence of nephrotoxicity from 6% to 21%, and the incidence is close to 30% with more than 2 weeks of therapy ( 2 ). Once-weekly monitoring of trough concentration is recommended in stable patients ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for vancomycin-associated nephrotoxicity can be divided into three classifi cations: vancomycin exposurerelated factors, host-related factors, and the use of concurrent nephrotoxins ( 1,2,8 ). Vancomycin exposure-related factors include larger vancomycin exposures, such as troughs >15 mg/L and prolonged duration of treatment.…”
Section: Discussionmentioning
confidence: 99%